2011
DOI: 10.1089/hum.2010.227
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Enhance Viral Penetration of Solid Tumors

Abstract: The efficient delivery of viral vectors to tumors is an active area of investigation. A number of barriers exist that must be overcome to achieve good penetration of vectors into tumors and distribution of their effects throughout the tumor mass. Replicating oncolytic viruses have the advantage of being able to amplify the initial dose, but progeny virus are prevented from spreading because of a dense mass of tightly packed cells with a dense extracellular matrix, admixed normal stromal cells, and high interst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 77 publications
1
48
0
Order By: Relevance
“…Systemic administration of naked DNA is also not recommended due to the presence of DNAase in the plasma (Borchard, 2001;Mao et al, 2001). Despite these advantages of intratumoral injections, this type of treatment can also be less than effective because of limited distribution of the injected agents (Sauthoff et al, 2003;Jia and Zhou, 2005;Smith et al, 2011;Zhao et al, 2011). In the present study, broader regions of necrosis were observed in the tumors treated with pFUS compared to the untreated ones, which correlated well with distributions of fluorescently labeled nanoparticles.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Systemic administration of naked DNA is also not recommended due to the presence of DNAase in the plasma (Borchard, 2001;Mao et al, 2001). Despite these advantages of intratumoral injections, this type of treatment can also be less than effective because of limited distribution of the injected agents (Sauthoff et al, 2003;Jia and Zhou, 2005;Smith et al, 2011;Zhao et al, 2011). In the present study, broader regions of necrosis were observed in the tumors treated with pFUS compared to the untreated ones, which correlated well with distributions of fluorescently labeled nanoparticles.…”
Section: Discussionsupporting
confidence: 68%
“…These include the use of tumor necrosis factor (TNF) related apoptosis-inducing ligand (TRAIL) for the treatment of lung cancer (Soria et al, 2010), granulocyte-macrophage colonystimulating factor (GM-CSF) for cutaneous melanoma (Mastrangelo et al, 1999), and interluekin-12 (IL-12) for metastatic melanoma (Triozzi et al, 2005). Despite the advantages of direct administration, this procedure still suffers from limited penetration and distribution of gene vectors (Sauthoff et al, 2003;Smith et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, dense extracellular matrix and the close proximity of cells to one another may be considered amongst the most prominent physical barriers that limit the movement of the relatively large particles, therefore the nanoshell spread within solid tumor may be limited and may rarely extend significantly beyond the site of injection. 45 One of the practical challenges in using an intratumoral injection to perform photothermal cancer therapy is to ensure that the injected nanoparticles evenly distribute throughout the whole tumor so that all of the cancerous cells can be killed by heat generated from the adjacent particles. Use of highresolution imaging techniques, such as PET and SPECT, can provide detailed intratumoral distribution information using a radiolabeled agent.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding intratumoral dissemination, the extracellular matrix (ECM) has a prominent role at inhibiting viral spread, acting as a physical barrier and raising the interstitial fluid pressure (IFP) in tumors (13)(14)(15). To tackle this problem, oncolytic viruses have been armed with ECM-degrading enzymes such as relaxin, decorin, metalloprotease-9, chondroitinase ABC (16)(17)(18)(19)(20), or PH20 hyaluronidase as we have previously reported (21).…”
Section: Introductionmentioning
confidence: 99%